Upregulation of miR-23b Enhances the Autologous Therapeutic Potential for Degenerative Arthritis by Targeting PRKACB in Synovial Fluid-Derived Mesenchymal Stem Cells from Patients - Ham, Onju; Lee, Chang Youn; Song, Byeong-Wook; Lee, Se-Yeon; Kim, Ran; Park, Jun-Hee; Lee, Jiyun; Seo, Hyang-Hee; Lee, Chae Yoon; Chung, Yong-An; Maeng, Lee-So; Lee, Min Young; et al. (Molecules and cells, 2014)
The use of synovial fluid-derived mesenchymal stem cells (SFMSCs) obtained from patients with degenerative arthropathy may serve as an alternative therapeutic strategy in osteoarthritis (OA) and rheumatoid arthritis (RA). For treatment of OA and RA patients, autologous transplantation of differentiated MSCs has several beneficial effects for cartilage regeneration including immunomodulatory activity. In this study, we induced chondrogenic differentiation of SFMSCs by inhibiting protein kinase A (PKA) with a small molecule and microRNA (miRNA). Chondrogenic differentiation was confirmed by PCR and immunocytochemistry using probes specific for aggrecan, the major cartilaginous proteoglycan gene. Absorbance of alcian blue stain to detect chondrogenic differentiation was increased in H-89 and/or miRNA-23btransfected cells. Furthermore, expression of matrix metalloproteinase (MMP)-9 and MMP-2 was decreased in treated cells. Therefore, differentiation of SFMSCs into chondrocytes through inhibition of PKA signaling may be a therapeutic option for OA or RA patients.